Targeting SLITRK4 Restrains Proliferation and Liver Metastasis in Colorectal Cancer via Regulating PI3K/AKT/NFκB Pathway and Tumor‐Associated Macrophage - Xiaojiao Sun; Junling Zhang; Bingqi Dong; Qingqing Xiong; Xin Wang; Yanlun Gu; Zhiqi Wang; Huiyu Liu; Jixin Zhang; Xu He; Hongjin Liu; Yi Zhong; et al. (Advanced Science)
Abstract Liver metastasis is the major cause of death in colorectal cancer (CRC) due to the lack of effective treatment. To explore novel drivers of CRC liver metastasis, the transcriptomes of primary paracancerous, colorectal tumors and metastases from human patients are profiled. It is found that SLIT‐ and NTRK‐like family member 4 (SLITRK4) is the top upregulated gene in liver metastases and is associated with worse overall survival of CRC patients. Multiple in vitro and in vivo models suggested SLITRK4 promoted CRC tumorigenesis, invasion, migration, and angiogenesis, and inhibition of it restrained CRC tumor growth and liver metastasis with a more profound effect on the tumor microenvironment (TME). Mechanistically, SLITRK4 overexpression significantly activated the PI3K/AKT/NFκB pathway, regulated extracellular matrix organization, and multiple cytokines expression. Furthermore, the results from coculture models and single‐cell RNA sequencing analyses suggested SLITRK4 promoted tumor‐associated macrophages (TAMs) infiltration and polarization. In addition, macrophage depletion significantly inhibited SLITRK4‐induced liver metastasis in CRC. Finally, pharmacological inhibition of SLITRK4 by using lipid‐polymer hybrid nanoparticles (NPs) for systemic siRNA delivery can effectively inhibit CRC liver metastasis. Taken together, these results pinpoint that SLITRK4 regulates CRC tumorigenesis and liver metastasis, and siRNA delivering NPs agents validate the therapeutic potential of targeting SLITRK4 in CRC.